INTERRELATION OF THE INCLUSIVE DEVELOPMENT INDEX SYSTEM AND CURRENT GDP & GDP BASED ON PPP INDICATORS - MAKHONIN, Vladyslav (Herald of Khmelnytskyi National University. Economic sciences, 2022)
This article is empirical in nature. Its purpose is to analyze, on the basis of a multivariate regression model, the question of the impact of the Inclusive Development Index–as the first index instrument of an inclusive economy–on such two forms of GDP as an indicator that the Inclusive Development Index was recognized to replace: current GDP per capita and GDP based purchasing power parity (given that the constant GDP indicator is officially included in the structure of the Index). The dimension of analysis described above and presented in this article is a component of the author’s research as part of a PhD program dedicated to determining the overall effectiveness of the Inclusive Development Index presented in 2017 by the World Economic Forum. The regression analysis showed the minimal presence of significant influences of the structure of the Inclusive Development Index on current GDP and GDP based on PPP as the two main economic indicators in the world. This allows us to talk about the abstract nature of the construction of the Inclusive Development Index.In turn, the inevitability of such aforementioned studies is dictated by the incompleteness of the reorientation of the model of global economic dynamics from the concept of sustainable development developed in the 1970s to the concept of inclusive economic growth. This, in particular, is declared today by specialists from leading international scientific and economic organizations and associations: The WEF, the OECD, the World Bank, The International Monetary Fund, The United Nations, and structures like the International Labor Organization and UNICEF, which operate under the auspices of the UN. The theoretical and practical significance of the results obtained may be useful in further studies on such composite indicators.
Keywords: inclusive economy; Inclusive Development Index; IDI; social and economic paradigm; types of GDP; regression analysis; macroeconomics; reorientation